MATHEMATICAL MODEL OF TRANSMISSION OF DATA IN THE MODE OF DETECTING THE ERRORS OF THE RECIPIENT WITH ACCOUNT OF FAILURES AT THE COMMUTATION NETWORKS IN NETWORKS OF AUTOMATED AIR TRAFFIC CONTROL SYSTEMS - Serhii A. Oberemok; Serhii V. Polishchuk (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
When transmitting information in modern networks of automated air traffic control systems, various methods of data exchange control are used, which is caused by the need to ensure the delivery time and the acceptable value of the equivalent error probability. In order to guarantee the delivery of messages, the reliability of the transmitted data is controlled, which is realized by using noise-immune encoding in detection or error correction modes with verification at each of the intermediate switching nodes or directly by the recipient. Thus, to study the probability-time characteristics of data exchange control methods in data exchange networks, it is necessary to analyze the process of packet transmission in the specified modes, taking into account the effect of intermediate switching nodes. In this case, in general, one should take into account both the presence of several data streams from other sources, and the possibility of failures in service at each of the switching nodes. The article describes a mathematical model of data transmission in the receiver error detection mode that allows to investigate the main probabilistic and temporal characteristics of the data transmission process in the networks of automated air traffic control systems in the mode of error detection taking into account additional information flows from other sources and possible failures at the switching nodes.